Genomics of Serratia marcescens Isolates Causing Outbreaks in the Same Pediatric Unit 47 Years Apart: Position in an Updated Phylogeny of the Species - Saralegui, Claudia; Ponce-Alonso, Manuel; Pérez-Viso, Blanca; Moles Alegre, Laura; Escribano, Esperanza; Lázaro-Perona, Fernando; Lanza, Val F.; de Pipaón, Miguel Sáenz; Rodríguez, Juan Miguel; Baquero, Fernando; del Campo, Rosa (Frontiers in Microbiology, 2020)
The first documented nosocomial outbreak caused by Serratia marcescens in Spain occurred in 1969 at the Neonatal Intensive Care Unit (NICU) of the tertiary La Paz Children’s Hospital in Madrid, Spain, and based on the available phenotyping techniques at this time, it was considered as a monoclonal outbreak. Only forty-seven years later, another S. marcescens outbreak of an equivalent dimension occurred at the same NICU. The aim of the present study was to study isolates from these historical and contemporary outbreaks by phenotypic analysis and whole-genome sequencing techniques, and to position these strains among 446 publicly available S. marcescens genomes, separately comparing core genome and accessory genome contents. Clades inferred by both approaches showed high correlation, indicating that core and accessory genomes seem to evolve in the same manner for S. marcescens. Considering nine S. marcescens clusters, isolates from both outbreaks grouped together in cluster 2 (mostly containing genomes of clinical strains with a very close accessory genome content), except for isolate 13F-69, that was the most genetically distant strain, located in cluster 1. However, within each outbreak, isolates showed genetic polymorphism and could be grouped by relatedness according to sampling period. In spite of this genetic heterogeneity, categorical functions were faithfully preserved in the annotated accessory genes of both collections. Slight differences in frequency of insertion sequences in historical (0.18-0.20, except in the outlier strain 13F-69, 0.53) versus contemporary isolates (0.11-0.19) can be attributed to the resting effect. The most dissimilar isolate, 13F-69, contains a highly preserved plasmid previously described in Bordetella bronchiseptica. This strain exhibited an antibiotic susceptible phenotype despite carrying 12 antibiotic resistance genes in its resistome, 4 of them plasmid-encoded, suggesting the value of gene silencing in adaptation to long-term starvation.